ABDUCENS NERVE PALSY AS THE FIRST MANIFESTATION OF NASOPHARYNGEAL MALIGNANCY - Hernandy Yuliawan, Handy; Kartika, Antonia; Hanindya Sari, Rusti (Fakultas Kedokteran Gigi Unjani, 2024)
Abducens Nerve Palsy is the most common ocular motor nerve palsy because the abducens nerve runs a long course from the brainstem to the lateral rectus muscle. Abducens Nerves palsy can result from several etiology; common etiologies of abducens palsy in adults include vascular disease, inflammation, tumours, and trauma. Therefore, early diagnosis is essential for some conditions that cause sixth nerve palsy. The purpose of this paper is to describe an isolated sixth nerve palsy as a first manifestation of Nasopharyngeal Malignancy. A 46-year-old female came to Cicendo Eye Hospital complaining of double vision from one month earlier, which would disappear if one eye was closed. The patient was diagnosed with Right Eye Abducens Nerve Palsy, which was suspected to be caused by ischemic then was asked to do an ischemic blood test and referred to an Internal Medicine Specialist. Three months after symptoms appeared, the patient returned to the clinic without any improvement and underwent a CT scan of the head with contrast and found an intracranial mass, suspected Nasopharyngeal Malignancy. Abducens nerve paralysis can be the first manifestation of a dangerous disease such as nasopharyngeal malignancy, so it takes awareness from every clinician when finding such cases. DOI : 10.54052/jhds.v4n2.p211-222